USAGE OF TECHNOLOGY IN HR PRACTICES IN HOTEL INDUSTRY, RADISSON BLU (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study aims at examining the usage of technology in HR practices inhotel industry. Technology is a tool that has and is still being globally used for thebenefit of humanity. It is being utilized by various hotel industries to meet the needsoffits various stakeholders. On are gular basis, new and upgraded versions oftechnology are being invented. It has been observed that, the distinguishing factorbetween organizations is their ability to use modern technology to deliver HR service.Technology in HR practice can be used to improve an organizations performance. In asmuch as technology has been of immense benefit to organizations, it also comes with itschallenges and other downsides. This study provides an outlay of how HR technologyemerged and its gradual acceptance and practice in hotel industry. The researchisintendedtoshowtheneedtounderstandtheuseoftechnologyinHRpracticesinhotelindustryandthe need to curbits challenges.